An Evaluation of Teaching Variation Skills in Increasing Students’ Learning Motivation - Zunidar Zunidar (Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to determine the skills of teachers in carrying out variations in learning, their impact on student motivation, and supporting factors and obstacles during the learning process. This research uses descriptive qualitative research. The data collection technique used is the method of observation, interviews, and documentation. The results of the study indicate that (1) The skills of teachers in conducting variations in the learning process have begun to be developed and are quite good. Teachers have been able to apply a varied learning process in order to provide enthusiasm for student learning, avoiding boredom and boredom in the teaching and learning process; (2) The use of teaching variations on student learning motivation greatly affects student activity in the classroom by making the student learning atmosphere more focused and enthusiastic; and (3) Student responses about the use of teaching variations on student learning motivation received a positive response from students' opinions, because it made the learning atmosphere comfortable, focused, and more enthusiastic by using teaching variations.